2013
DOI: 10.1371/journal.pone.0084474
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Inhibits Ascorbate Recycling and Light Stimulation of the Ascorbate Pool in Tomato despite Increased Expression of Biosynthesis Genes

Abstract: Understanding how the fruit microclimate affects ascorbate (AsA) biosynthesis, oxidation and recycling is a great challenge in improving fruit nutritional quality. For this purpose, tomatoes at breaker stage were harvested and placed in controlled environment conditions at different temperatures (12, 17, 23, 27 and 31°C) and irradiance regimes (darkness or 150 µmol m-2 s-1). Fruit pericarp tissue was used to assay ascorbate, glutathione, enzymes related to oxidative stress and the AsA/glutathione cycle and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 62 publications
5
31
0
1
Order By: Relevance
“…In tomato fruits, it has been shown that under conditions of high-temperature stress, the CAT enzymatic activity increases [73]. Similar results were obtained in tomato leaves [75]. Therefore, the increase in CAT activity has a positive response in fruits.…”
Section: Bioactive Compoundssupporting
confidence: 68%
“…In tomato fruits, it has been shown that under conditions of high-temperature stress, the CAT enzymatic activity increases [73]. Similar results were obtained in tomato leaves [75]. Therefore, the increase in CAT activity has a positive response in fruits.…”
Section: Bioactive Compoundssupporting
confidence: 68%
“…It has been shown for Vicia faba that young seeds are not capable of producing AsA and are provided with AsA by the maternal tissues (Arrigoni et al 1992). Moreover, studies in tomato have shown that AsA can be transported from leaves to fruits (Giovanelli et al 1999;Massot et al 2013;Stevens et al 2007). …”
Section: Osgme and Osggp-dependent Asa Levels Play A Role In The Devementioning
confidence: 99%
“…Ascorbate concentrations were reported to be limited during green fruit development , which is also the stage of BER appearance (Spurr, 1959). Ascorbate concentration in tomato fruit was also found to be reduced under high salinity (D'Amico et al, 2003), heat (Massot et al, 2013) and light stress conditions (Ioannidi et al, 2009;, all conditions favorable for BER appearance (Olle and Bender, 2009). Interestingly, fruit calcium concentration, the major known factor in BER initiation, has also been proposed to be positively correlated with ascorbate levels in tomato fruit (Premuzic et al, 1998) and the conditions favorable to BER, like salinity, drought and heat stress, were also found to increase ROS levels in tomato fruit (Leyva et al, 2013;Murshed et al, 2013Murshed et al, , 2014.…”
Section: Introductionmentioning
confidence: 98%